2016
DOI: 10.1007/s10107-016-1001-y
|View full text |Cite
|
Sign up to set email alerts
|

A cross-decomposition scheme with integrated primal–dual multi-cuts for two-stage stochastic programming investment planning problems

Abstract: We describe a decomposition algorithm that combines Benders and scenariobased Lagrangean decomposition for two-stage stochastic programming investment planning problems with complete recourse, where the first-stage variables are mixedinteger and the second-stage variables are continuous. The algorithm is based on the cross-decomposition scheme and fully integrates primal and dual information in terms of primal-dual multi-cuts added to the Benders and the Lagrangean master problems for each scenario. The potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Algorithms based on the single-search-tree strategy often use this approach to tighten the root node and reduce the size of the tree (see e.g., Botton et al, 2013). Cross-decomposition has received much less attention, although a recent study by Mitra et al (2016) has demonstrated that it can be superior to the BD method when the underlying LP relaxation is weak. Stabilization techniques significantly reduce the number of iterations, but the cost of each iteration may increase because of the additional complexities that they introduce in the MP.…”
Section: Alternative Formulationmentioning
confidence: 99%
“…Algorithms based on the single-search-tree strategy often use this approach to tighten the root node and reduce the size of the tree (see e.g., Botton et al, 2013). Cross-decomposition has received much less attention, although a recent study by Mitra et al (2016) has demonstrated that it can be superior to the BD method when the underlying LP relaxation is weak. Stabilization techniques significantly reduce the number of iterations, but the cost of each iteration may increase because of the additional complexities that they introduce in the MP.…”
Section: Alternative Formulationmentioning
confidence: 99%
“…In addition to the above constraints, the non-anticipativity constraints are assumed for the first stage variables: their value is the same for all scenarios [51,52]. With these constraints, it is assumed that the decision should depend only on information available at the time of the decision and not on future observations [53,54].…”
Section: Constraintsmentioning
confidence: 99%
“…When considering a deterministic equivalent problem for the two-stage stochastic model of the supply chains, the objective function is defined by the following relation [53,54,64] (see Equation ( 23)):…”
Section: Objective Functionmentioning
confidence: 99%
“…Directly using an optimization solver to handle all scenarios simultaneously is not efficient because its computational time grows exponentially as the number of scenarios increases. Several decomposition strategies thus have been developed to solve each scenario separately, for example, Lagrangian decomposition, 23−25 Benders decomposition, 26,27 and cross decomposition; 29 their computational time grows linearly as the number of scenarios increases. A more complicated case, which combines the chance constraints and two-stage stochastic program, is proposed by Liu et al 30 for the two-stage decision process with dual mode operations.…”
Section: Introductionmentioning
confidence: 99%